Impact of ventilation and ambient temperature on COVID-19 transmission in clinic waiting rooms: A computational fluid dynamics approach. - Zhankun Zhu; Guosheng Gao; Yaoren Hu; Xiansheng Zhao (PLoS ONE)
The ongoing COVID-19 pandemic underscores the necessity of understanding the transmission dynamics in enclosed, high-risk environments, such as clinic waiting rooms. This study used computational fluid dynamics (CFD) to investigate the behavior of virus-laden aerosols in clinic waiting rooms under six different scenarios with various temperatures and ventilation setups, offering insights into practical strategies for enhancing safety in healthcare environments. Key findings demonstrated that effective ventilation, through open windows and mechanical systems, can reduce virus-laden aerosol concentrations by up to 99.3% under optimal conditions (e.g., from 5.80 kg/m3 to 0.04 kg/m3By contrast, poorly ventilated scenarios exhibit significantly higher viral concentrations, which can rise as high as 5.80 kg/m3. A novel aspect of this research lies in the comprehensive modeling of human anatomy and aerosol interactions, which enhances the accuracy of viral-trajectory predictions. The practical implications include strategic recommendations for ventilation system design to mitigate transmission risks in clinical settings. These insights provide guidelines for healthcare facility design and emphasize the critical role of environmental control in reducing exposure to airborne pathogens.